Pengaruh Edukasi Gizi terhadap Pengetahuan dan Sikap tentang 1000 Hari Pertama Kehidupan pada Catin Wanita di Wilayah Kerja KUA Kecamatan Abeli - Subu, Anisa Maharael; Ananda, Siti Hadrayanti; Demmalewa, Jenny Qlifianti (Jurnal Gizi Ilmiah, 2022)
Nutritional education for the first 1000 days of life is an education that contains the preparation and improvement of nutrition from 270 days during pregnancy and the first 730 days of life since the baby is born. This study aims to determine effect of nutritional education on knowledge and attitudes about the First 1000 Days of Life in future bride in Abeli’s religious affairs office. This research is a type of pre-experimental, with a One Group Pre-Post Test design. The sample in this study were 39 female catin in the KUA working area of ​​Abeli ​​District which were obtained by sampling technique using the Slovin formula. The variables studied consisted of the dependent variable, namely knowledge and attitudes, and the independent variable, namely nutrition education in the first 1000 days of life. Data analysis using Wilcoxon (α = <0.05)The results of the research show that the p value of the knowledge and attitude variables is 0.000 < α (0.05 ). The conclusion of this study is that there is an effect of nutritional education in the first 1000 days of life in knowledge and attitudes of future bride in Abeli’s religious affairs office.